2021
DOI: 10.3390/polym13183149
|View full text |Cite
|
Sign up to set email alerts
|

Nonedible Vegetable Oil-Based Polyols in Anticorrosive and Antimicrobial Polyurethane Coatings

Abstract: This review describes the preparation of nonedible vegetable oil (NEVO)-based polyols and their application in anticorrosive and antimicrobial polyurethane (PU) coatings. PUs are a class of versatile polymers made up of polyols and isocyanates. Renewable vegetable oils are promising resources for the development of ecofriendly polyols and the corresponding PUs. Researchers are interested in NEVOs because they provide an alternative to critical global food issues. The cultivation of plant resources for NEVOs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 177 publications
(244 reference statements)
0
18
0
Order By: Relevance
“…Ibrahim, et al [25], previously reported an alkyd resin production range of 2.56-23.93 %. However, when compared to the results for ordinary alkyd resin production in the literature [26][27][28][29][30][31][32][33][34][35], the optimized experimental yields reported in this work were both greater. We were able to obtain a successful combination of input variables using the Box-Behnken Design Response Surface Methodology, which resulted in better yields and quality that were comparable to commercially available alkyd resins, resulting in the study's novel outcomes.…”
Section: Refined Sesame Based Alkyd Resinmentioning
confidence: 58%
“…Ibrahim, et al [25], previously reported an alkyd resin production range of 2.56-23.93 %. However, when compared to the results for ordinary alkyd resin production in the literature [26][27][28][29][30][31][32][33][34][35], the optimized experimental yields reported in this work were both greater. We were able to obtain a successful combination of input variables using the Box-Behnken Design Response Surface Methodology, which resulted in better yields and quality that were comparable to commercially available alkyd resins, resulting in the study's novel outcomes.…”
Section: Refined Sesame Based Alkyd Resinmentioning
confidence: 58%
“…Finally, the solid was vacuum-dried. After dissolving in a mixture of toluene and ethanol (1:1), the acid value of in-process samples taken at intervals was determined by titrating with a 0.1 M KOH solution to the phenolphthalein end point [9].…”
Section: Esterification Stagementioning
confidence: 99%
“…Each sample was weighed into conical flasks at a weight of 5 g. Each of the solvents was added separately in 5 mL increments, and the mixture was vigorously shaken. The solubility of each mixture was measured after it had been allowed to stand for 1 hour at room temperature [9].…”
Section: Solubility Testmentioning
confidence: 99%
See 2 more Smart Citations